Pengaruh Budaya Organisasi, Pelatihan Dan Motivasi Kerja Terhadap Produktivitas Kerja (Studi Kasus Pada PT. Kenbry Marmer Pratama Kota Tangerang) - Aris, Aris Wahyu Kuncoro; Hasan Ipmawan; Dwi Kristanto; Pambuko Naryoto; Koen Hendrawan; Natasya Islami Passya (Pusat Riset dan Inovasi Nasional, 2024)
The occurrence of employee decline and increase is not solely attributed to the employees themselves. Hence, this indicates the need for further research on the organizational culture, training, and job motivation at PT. Kenbry Marmer Pratama in Tangerang City. The objective of this study is to determine the influence of culture, training, and job motivation on the work productivity of employes at PT. Kenbry Marmer Pratama in Tangerang City. The research method employed is quantitative. The population in this study consists of all employees at PT. Kenbry Marmer Pratama in Tangerang City. The sample in this study is a saturated sample, comprising 35 respondents. The results of this study indicate that organizational culture does not have a significant influence on work productivity at PT. Kenbry Marmer Pratama in Tangerang City. However, training has a significant influence on work productivity at PT. Kenbry Marmer Pratama in Tangerang City. Additionally, job motivation also has a significant influence on work productivity at PT. Kenbry Marmer Pratama in Tangerang City.